B vitamin intakes modify the association between particulate air pollutants and incidence of all‐cause dementia: Findings from the Women's Health Initiative Memory Study. Issue 11 (1st February 2022) - Chen, Cheng; Whitsel, Eric A.; Espeland, Mark A.; Snetselaar, Linda; Hayden, Kathleen M.; Lamichhane, Archana P.; Serre, Marc L.; Vizuete, William; Kaufman, Joel D.; Wang, Xinhui; Chui, Helena C.; D'Alton, Mary E.; et al.
Abstract: Introduction: Particulate air pollutants may induce neurotoxicity by increasing homocysteine levels, which can be lowered by high B vitamin intakes. Therefore, we examined whether intakes of three B vitamins (folate, B12, and B6 ) modified the association between PM2.5 exposure and incidence of all‐cause dementia. Methods: This study included 7183 women aged 65 to 80 years at baseline. B vitamin intakes from diet and supplements were estimated by food frequency questionnaires at baseline. The 3‐year average PM2.5 exposure was estimated using a spatiotemporal model. Results: During a mean follow‐up of 9 years, 342 participants developed all‐cause dementia. We found that residing in locations with PM2.5 exposure above the regulatory standard (12 μg/m 3 ) was associated with a higher risk of dementia only among participants with lower intakes of these B vitamins. Discussion: This is the first study suggesting that the putative neurotoxicity of PM2.5 exposure may be attenuated by high B vitamin intakes.